2022
DOI: 10.1108/cg-12-2020-0565
|View full text |Cite
|
Sign up to set email alerts
|

The development of corporate governance literature in Malaysia: a systematic literature review and research agenda

Abstract: Purpose This study aims to provide a comprehensive review of the existing literature on corporate governance (CG) aspects of the Malaysian market. It offers insights into the phases of Malaysian CG, identifies crucial gaps in the literature and outlines an agenda for impending research. Design/methodology/approach Following a systematic literature review approach, a final sample of 125 studies from Scopus and Web of Science databases was used in this study. These studies were selected based on quality assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 149 publications
1
54
0
2
Order By: Relevance
“…SFSCs may operate in different models: farmers' markets, pick-yourown, on-farm sales, community-supported agriculture, or through an intermediary [33]. In addition, with increased web-based sales, SFSCs may include direct internet sales that could involve non-local sales [35]. Generally, producers and consumers are the two most important actors defining SFSCs.…”
Section: Food Supply Chains: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…SFSCs may operate in different models: farmers' markets, pick-yourown, on-farm sales, community-supported agriculture, or through an intermediary [33]. In addition, with increased web-based sales, SFSCs may include direct internet sales that could involve non-local sales [35]. Generally, producers and consumers are the two most important actors defining SFSCs.…”
Section: Food Supply Chains: Overviewmentioning
confidence: 99%
“…Furthermore, discussion about the long-term impact of the COVID-19 pandemic on consumer perceptions will continue to attract attention. Due to variations in government restrictions and the impact of the pandemic, evidence may vary across time and geography [35]. Thus, context-specific studies are paramount to expanding our understanding of consumer behavior and the impact of the pandemic on consumer perceptions of SF-SCs.…”
Section: Past External Events On Consumer Perceptions and Shopping Be...mentioning
confidence: 99%
“…The CSR performance can be measured using the ESG score, which is considered a proxy for the firm results on CSR practices [6,7] because it provides the most objective measure available at the time of writing. In fact, the ESG score is intended to objectively and clearly evaluate the ESG performance, considering the bundle of environmental and social activities of CSR, together with the corporate governance activities [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This search string helped to collect most of the studies that have a combination of keywords related to Shariah and auditing. This method was applied in several prior SR research (Khatib et al, 2022;Khatib et al, 2021bKhatib et al, , 2021cSahi et al, 2021;Hazaea et al, 2021a;Zamil et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Up to date, to the best of the authors’ knowledge, there is no study that provided a systematic review (SR) to assess the SA research. Consequently, conducting a comprehensive study using SR based on previous studies might be an essential way to highlight the gaps in the field and provide insights for future research (Khatib et al , 2022). It has been suggested that the need for a new study is not as great as the need for the assimilation of already existing studies.…”
Section: Introductionmentioning
confidence: 99%